ABC based reduced order modelling of microgrid in grid-tied mode. (March 2019) - Juneja, Mudita; Nagar, S.K.; Mohanty, Soumya R.
Abstract: Artificial Bee Colony (ABC) algorithm inspired from honeybee optimization in food search, provides an optimum reduced order model for complex grid-tied microgrid system. The paper aims to develop the best second-order model for a fifteenth order microgrid system in a grid-tied mode such that it closely replicates the original system. The comparative study of ABC reduced order model along with some other reduced order models of grid-tied microgrid system in time and frequency domain proves its suitability particularly in terms of least error in reduction and faster convergence. Eigenvalue stability has been discussed in different cases of perturbation and participation analysis.